Gas transfer in rainbow trout (Oncorhynchus mykiss): An investigation of factors controlling oxygen(2) uptake and carbon dioxide excretion. - Desforges, Patrick J. R. C. (University of Ottawa (Canada), 2001)
The entry of bicarbonate ions (HCO3-) into the red blood cell (RBC) via the Cl-/HCO3 - exchanger for dehydration to CO2 has long been regarded as the limiting step of CO2 excretion in fish. The first component of this thesis was to test the hypothesis that proton availability may limit the catalysed dehydration of HCO3- within the extracellular compartment. The results presented in this thesis suggest that H+ availability does not appear to limit plasma HCO3- dehydration in vivo. Furthermore, the enhancement of CO2 excretion by means of the acceleration of HCO3- dehydration within the plasma following the administration of carbonic anhydrase (CA) demonstrated in this thesis was the first in vivo evidence ratifying the hypothesis of the chloride shift as the limiting factor on CO2 excretion in teleost fish. Using the knowledge acquired from the previous chapter, I tested the hypothesis that the slow entry rate of HCO3- into the RBC may be responsible for the apparent diffusion limitations on CO2 excretion. The experiments examined the effect of blood transit time through the gills on gas transfer to test the hypothesis that the efficiency of CO2 excretion is sensitive to changes in blood flow owing to chemical equilibrium limitations, whereas the efficiency of O2 uptake is insensitive to changes in blood flow. The insensitivity of PaO 2 to changes in cardiac output in vivo reaffirms the theory that O2 uptake behaves as a perfusion limited system. However, the sensitivity of CO2 transfer efficiency to changes in cardiac output, coupled with the impact of (CA) availability on this sensitivity, argue strongly that the apparent diffusion limitations on CO2 excretion are, in fact, chemical equilibrium limitations.
Keywords: Biology, Animal Physiology.